Immunotherapy in the prevention and management of COVID-19: pros and cons of a race against time - Ríos, Leonor (2020)
As war correspondents, investigators face the challenge of reporting on a daily basis the confrontation with SARS-CoV-2, a virus that has put public health and the socio-economic structure of virtually all countries at collapse edge. Basic rules of hygiene and the social isolation are valuable weapons in the strategic plan of this battle. However, to limit the spread of the virus and manage the disease it produces (COVID-19), it is tactical to understand the dual role of the immune response in infected individuals. On the one hand, the molecular and cellular actors of the immune system are, without a doubt, determining factors in the control of infection and viral replication; on the other hand, its contribution to COVID-19 severity and mortality has also been evidenced. Consequently, the design and implementation of immunotherapy strategies to manipulate the immune system, as well as the identification of immunological biomarkers with prognostic value, are a priority in the prevention and management of this disease. The accumulated experience and also the opportunities offered by genetic engineering in the design of vaccination platforms and other biological therapies, are determining factors. However, the stages and time frames that regularly require the development of these products are not compatible with the rapid control of this pandemic. What risks do we face when a pandemic forces us to modify the development strategy of a therapeutic weapon? This paper addresses the relevance of immunotherapy against SARS-CoV-2 and the challenges of its development in the middle of this war.